(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Every activity requires a certain amount of concentration and no effective action may be performed without deep concentration. Businessman or artists or students in school must know the art of focusing all powers of attention on a single point in order to succeed in their respective vocation. Methods: We wanted to find the best technique to increase the concentration scientifically. We thus, endeavored to study and compare the reaction times in maneuvers of anuloma viloma pranayama, kapalbhatti pranayama, gayatri chanting and exercise. Reaction time test was taken online before anuloma viloma pranayama, kapalbhatti pranayama, gayatri chanting and exercise and compared after. Results: Reaction times decreased significantly and was least during gayatri mantra. Concentration as seen by a decrease in visual reaction time denotes first a withdrawal of attention from objects of distraction and then focusing all attention upon one thing at a time. Just 30 minutes of physical activity each day offers substantial benefits to your health. Conclusions: Pranayama or devotional music chanting also decreases fatigue keeps the mind alert, and active. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.596-600